1985
DOI: 10.1212/wnl.35.8.1152
|View full text |Cite
|
Sign up to set email alerts
|

Reversible chronic cerebellar ataxia after phenytoin intoxication

Abstract: Reversible chronic cerebellar ataxia followed phenytoin treatment in two epileptic women. Cerebellar ataxia in both patients and axonal polyneuropathy in one patient were improved after administration of thiamine alone or with folate. In one patient, some specific behavioral functions improved. However, recovery could have been spontaneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(47 citation statements)
references
References 0 publications
1
45
1
Order By: Relevance
“…Patients with cerebellar cortical atrophy were found to have impaired executive function demonstrated by increased planning time on the Tower of Hanoi Test [Grafman et al 1992], and by poor performance on tests of fluency and the initiation/ perseveration subtest of the Mattis Dementia Rating Scale [Appollonio et al 1993]. Visual spatial deficits were described following excision of left cerebellar hemisphere tumors [Wallesch and Horn 1990], as well as in the setting of chronic phenytoin intoxication [Botez et al 1985], and after left superior cerebellar artery territory infarction [Botez-Marquard et al 1994]. Linguistic processing was impaired in patients with right cerebellar infarction, with symptoms including agrammatism [Silveri et al 1994] and impaired linguistic error detection [Fiez et al 1992].…”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%
“…Patients with cerebellar cortical atrophy were found to have impaired executive function demonstrated by increased planning time on the Tower of Hanoi Test [Grafman et al 1992], and by poor performance on tests of fluency and the initiation/ perseveration subtest of the Mattis Dementia Rating Scale [Appollonio et al 1993]. Visual spatial deficits were described following excision of left cerebellar hemisphere tumors [Wallesch and Horn 1990], as well as in the setting of chronic phenytoin intoxication [Botez et al 1985], and after left superior cerebellar artery territory infarction [Botez-Marquard et al 1994]. Linguistic processing was impaired in patients with right cerebellar infarction, with symptoms including agrammatism [Silveri et al 1994] and impaired linguistic error detection [Fiez et al 1992].…”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%
“…The view that the cerebellum coordinates the direction of selective attention and as a consequence subserves the execution of cortically generated commands for the enhancement and inhibition of different sources of sensory information has been confirmed in large series of behavioral, neurophysiological, and neuroimaging studies (Courchesne, 1985;Thompson, 1986;Akshoomoff & Courchesne, 1994;Le & Hu, 1996;Akshoomoff, Courchesne, & Townsend, 1997). Botez, Gravel, Attig, and Vézina (1985) first underscored the role of cerebellofrontal and cerebelloparietal associative loops as neural substrates of mild frontal-and parietal-like symptoms encountered in a patient with reversible cerebellar ataxia after chronic phenytoin intoxication. Many of their subsequent studies further explored the role of the cerebellum in visuospatial and visuoconstructive procedures (Botez, Léveillé, Lambert, & Botez, 1991;Botez-Marquard & Botez, 1993;Botez-Marquard, Léveillé, & Botez, 1994;Botez-Marquard & Routhier, 1995;Botez-Marquard, Pedraza, & Botez, 1996).…”
mentioning
confidence: 92%
“…For a long period of time, the scientific community considered the cerebellum to have an exclusive motor function. It is only recently that neuroanatomical and clinical evidence suggested that the cerebellum also plays an important role in cognitive function (in particular, Botez, Gravel, Attig, & Vezina, 1985;Leiner, Leiner, & Dow, 1986;Schmahmann, 1991). Schmahmann and Sherman (1998) further clarified the nonmotor role of the cerebellum, describing the cerebellar cognitive affective syndrome (CCAS).…”
Section: Introductionmentioning
confidence: 99%